2004
DOI: 10.1179/147842204225016859
|View full text |Cite
|
Sign up to set email alerts
|

Origins of pitting corrosion

Abstract: Corrosion of metals and alloys by pitting constitutes one of the very major failure mechanisms. Pits cause failure through perforation and engender stress corrosion cracks. Pitting is a failure mode common to very many metals. It is generally associated with particular anions in solution, notably the chloride ion. The origin of pitting is small. Pits are nucleated at the microscopic scale and below. Detection of the earliest stages of pitting requires techniques that measure tiny events. This paper describes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
149
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(159 citation statements)
references
References 14 publications
7
149
0
3
Order By: Relevance
“…The formation and development of this type of attack on the metal surface can occur only in solutions containing the aggressive Cl -, Br -and I -ions [4][5][6][7][8][9][10][11][12] . The critical potential at which pitting initiates is reported by several authors and found to depend on a number of factors including the type and concentration of attacking anion, type of metal used and relative concentration of other anions [13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…The formation and development of this type of attack on the metal surface can occur only in solutions containing the aggressive Cl -, Br -and I -ions [4][5][6][7][8][9][10][11][12] . The critical potential at which pitting initiates is reported by several authors and found to depend on a number of factors including the type and concentration of attacking anion, type of metal used and relative concentration of other anions [13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…32,44,45 Three potential levels, i.e., 250, 350, and 450 mV SCE were selected for potentiostatic tests based on CPP results (Figure 7a). At 450 mV SCE , stable pitting corrosion occurred on the control sample (Figure 8a) with high current (mA).…”
Section: Resultsmentioning
confidence: 99%
“…For passive metals, such as stainless steels and aluminium, the effect of secondary constituents in pit initiation is well-known [21]. For mild and low alloy steels, however, secondary constituents usually are considered in terms of their effect on corrosion products and the consequent effect on corrosion as controlled by oxygen diffusion limitations.…”
Section: Background To Cathodic Competitionmentioning
confidence: 99%